Adverse Impact of Racial Isolation on Student Performance: A Study in North Carolina - Sharma, Andy; Joyner, Ann Moss; Osment, Ashley (Education Policy Analysis Archives, 2014)
This study examines the impact of racial isolation on high school student performance in North Carolina, a state in the southeast United States. Our research goal is to investigate if increased isolation negatively impacts Black students’ academic performance. Employing the North Carolina State Department of Public Instruction (NCDPI) dataset, we test for this using Algebra I and English I scores on End-of-Course exams for ninth graders (N = 134,646) during the 2007-2008 school year. We control for student-level characteristics, such as race and ethnicity, economic disadvantage (eligibility for free and reduced-price lunch), and designation as gifted. We also analyze the effect of school-level characteristics, such as teacher experience, teacher training (advanced degree), teacher accreditation (fully licensed), and the percentage of students who were Black or Latino. Our results suggest racial isolation adversely impacts student performance on Algebra I by as much as three points. With our restricted hierarchical dataset and multi-level modeling, we (a) contribute to the growing body of literature, which finds a negative association between racial isolation/segregation and student performance, and (b) find teacher attributes can moderate some of the adverse student outcomes.